Is Every Pole a Catholic? – the Borderland Quandaries of Nationality and Religion Faced by Russian Bureaucracy in a 1910 Ministry of Internal Affairs Document - Jurkowski, Roman (Studia z Dziejów Rosji i Europy Środkowo-Wschodniej, 2018)
Is Every Pole a Catholic? – the Borderland Quandaries of Nationality and Religion Faced by Russian Bureaucracy in a 1910 Ministry of Internal Affairs Document Abstract During the long process of introduction of zemstva (organs of local government) to the Western guberniyas of Russia (began in 1906), there was once again the problem of domination of Polish landlords within the social structures as well as political and economic life of Belarusian and Ukrainian guberniyas. The tsarist authorities, who sought to ensure the dominance of a few Russian landowners in the electoral laws to zemstva, had to set up such an electoral system that would make it possible to reduce in zemstwa the number of Polish nobility. To do so, it was necessary to determine with precision who, according to laws, was “a person of Polish origin”. Prime Minister Pyotr Stolypin, preparing the introduction of national curias for the elections to Western zemstva, ordered an official of the Ministry of Internal Affairs to work out a memorial describing all the methods used after the fall of the January Uprising to distinguish Polish landowners from all the members of this class. The memorial by Alexandr Strolman, presented here in its original form and in translation to the Polish language, is a historic review of all actions taken both by local and central authorities to establish basic criteria necessary to determine and distinguish all Polish landowner from among all the landowners in Western guberniyas of Russia. Каждый ли католик - поляк? Кресовые, национально-религиозные дилеммы российской бюрократии в документе Министерства Внутренних Дел 1910 года Аннотация Во время длинного процесса введения земств в западных губерниях России (начатого в 1906 году) в очередной раз возникла проблема доминирования польских помещиков в общественных структурах, а также в политической и экономической жизни белорусских и украинских губерний. Власти, стремясь к обеспечению преимущества немногочисленным российским землевладельцам в земской избирательной системе, должны были создать такую систему, которая позволила бы сократить в ней число польских помещиков. Чтобы сделать это, надо было сначала точно определить, кто, в свете закона, считается «лицом польского происхождения». Премьер-министр Петр Столыпин, подготавливая введение национальных курий в выборах в западные земства, поручил чиновнику Министерства внутренних дел подготовить докладную записку, объясняющую, какими методами, в период после Январского восстания, государственные власти выделяли польских помещиков из всех представителей этой социальной группы. Докладная записка Александра Строльмана, напечатанная в подлиннике и в переводе на польский, является историческим обзором действий центральной и провинциальной администраций, направленных на определение основных критериев, отличающих поляков от всех остальных землевладельцев в западных губерниях России.